2018
DOI: 10.1371/journal.pone.0191268
|View full text |Cite
|
Sign up to set email alerts
|

Yearly fluctuations of flower landscape in a Mediterranean scrubland: Consequences for floral resource availability

Abstract: Species flower production and flowering phenology vary from year to year due to extrinsic factors. Inter-annual variability in flowering patterns may have important consequences for attractiveness to pollinators, and ultimately, plant reproductive output. To understand the consequences of flowering pattern variability, a community approach is necessary because pollinator flower choice is highly dependent on flower context. Our objectives were: 1) To quantify yearly variability in flower density and phenology; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 71 publications
0
27
0
Order By: Relevance
“…At that time, flower visitation rates are low compared to late spring, when floral resources sharply decline and a greater number of pollinator species are active (Bosch et al 2009, Filella et al 2013. Therefore, floral resources are more likely to become limiting as the season progresses (Flo et al 2018). A previous study in the same area encompassing the entire flowering season found evidence of displacement of wild pollinator communities (especially large bees) by honey bees (Torné-Noguera et al 2016).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…At that time, flower visitation rates are low compared to late spring, when floral resources sharply decline and a greater number of pollinator species are active (Bosch et al 2009, Filella et al 2013. Therefore, floral resources are more likely to become limiting as the season progresses (Flo et al 2018). A previous study in the same area encompassing the entire flowering season found evidence of displacement of wild pollinator communities (especially large bees) by honey bees (Torné-Noguera et al 2016).…”
Section: Discussionmentioning
confidence: 96%
“…Because as much as 99.1% of honey bee visits were on R. officinalis and T. vulgaris, it is unlikely that honey bees could have any competitive effects on pollinators visiting other, less abundant, flower species. This result may be related to the time of the year (early spring) in which surveys were conducted, corresponding to the peak of flower production in the park (Flo et al 2018). At that time, flower visitation rates are low compared to late spring, when floral resources sharply decline and a greater number of pollinator species are active (Bosch et al 2009, Filella et al 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the tallgrass prairie community, Echinacea tends to flower mid-season. However, there can be high year-to-year variation in the pattern and abundance of co-flowering species (Flo et al 2018). In addition, as the flowering season progresses, the proportion of Echinacea heads that have finished shedding pollen increases.…”
Section: Temporal Variation In Pollinator Community Composition and Fmentioning
confidence: 99%
“…It also shows seasonality in the availability of food resources for cavity-nesting bees (pollen and nectar) and wasps (insect and spider prey). Pollen and nectar are much more abundant in spring [ 31 , 32 ], whereas arthropod preys (aphids, caterpillars and spiders) are more abundant in summer [ 33 – 36 ]. For these reasons, and given that solitary bees and wasps usually have short activity periods [ 37 39 ], we expect high species and functional trait turnover across seasons.…”
Section: Introductionmentioning
confidence: 99%